Legal Basis for Ensuring Economic Security in the People’s Republic of China - Li, Pan; Ivanytska, Olga (Theory and Practice of Public Administration, 2024)
This study is aimed at analyzing the economic security management system in the People’s Republic of China (PRC). The purpose of the publication is to determine the evolution of the legal framework for the formation of China’s economic security system, as well as scientific efforts in this area. The author reveals the key approaches of Chinese scholars to understanding economic security, and reflects the disclosure of various aspects of national and economic security in the Constitution of the People’s Republic of China and numerous legal acts. The methodology of the article is based on the use of the methods of analysis and synthesis, retrospective analysis, modeling, legal analysis, induction and deduction. The scientific novelty of the article is to substantiate the criteria for studying the paradigm shift in ensuring economic security as part of China’s national security and, on this basis, to identify four stages of development of the institutional framework for ensuring economic security in the Chinese State. The paper analyzes in detail the concepts and ideas of achieving economic security that have developed in the scientific community of China. The author examines the trends in changes in state policy on national security and the development of social relations in the context of the growing importance of economic security. The authors also study the overall system of economic security, analyze its components and mechanisms of interaction between them. The authors emphasize the transition from the traditional concept of national security, which is mainly based on the military sphere, to a new paradigm with an emphasis on ensuring the economic stability of the country. The author presents the system of Chinese legal acts regulating activities related to national economic security. Particular attention is paid to the possibility of comparing the results of this study with other similar studies in order to develop clearer guidelines for theoretical research and practical activities in the field of national economic security. From the methodological point of view, the article uses a dialectical approach that combines theoretical research methods from various sciences (history, legal analysis) to ensure the depth and breadth of the analysis. The study concludes that strengthening administrative and legal support for economic security will help strengthen China’s position both domestically and internationally. For Ukraine, the approach adopted by the Chinese government will help clarify some theoretical concepts and aspects of economic security practices, providing guidance for the public administration in addressing common problems related to national security.